Impact of Service Quality and Policy Coverage Value on Customer Satisfaction at PT. FTI - Sakinah; Syarvina, Wahyu; Rahma, Tri Indah Fadhila (Jurnal Manajemen Bisnis, 2024)
This study aims to examine the influence of Service Quality and Policy Coverage Value on Customer Satisfaction at PT. FTI, both partially and simultaneously. Employing a quantitative approach, data collection was conducted using a Likert scale method. The subjects comprised 40 customers from the Medan branch of PT. FTI, selected through random sampling. Data analysis was performed using IBM SPSS Statistics 26. Results indicate that: Firstly, Service Quality significantly and positively affects Customer Satisfaction with a significance value of 0.042 less than 0.05. Secondly, Policy Coverage Value also significantly and positively influences Customer Satisfaction with a significance value of 0.031 less than 0.05. Thirdly, both Service Quality and Policy Coverage Value collectively have a significant positive impact on Customer Satisfaction, with a significance value of 0.028 less than 0.05.